Cross-Cultural Adaptation And Psychometric Validation Of The Columbia Suicide Severity Rating Scale (Lifetime/Recent- Clinical Version) Into Bangla - Rahman , Dr. Jebun Nahar, Dr. Nusrat Jahan Tanzilla, Dr. Mohsin Ali Shah, Dr. Mahabuba (South Eastern European Journal of Public Health, 2025)
Background: Suicidal behavior, including ideation, attempts, and non-suicidal self-injury (NSSI), represents a major public health challenge globally, particularly in low- and middle-income countries like Bangladesh. Despite the widespread use of the Columbia-Suicide Severity Rating Scale (C-SSRS) for suicide risk assessment, a validated Bangla version of the C-SSRS Lifetime/Recent - Clinical version is currently lacking. Aim of the study: To translate, culturally adapt, and validate the Bangla version of the Columbia-Suicide Severity Rating Scale (C-SSRS) Lifetime/Recent – Clinical version for the assessment of suicidal ideation and behaviors in Bangladeshi adolescents and adults. Methods: A cross-sectional study was conducted from October 2021 to September 2023 at the Department of Psychiatry, BSMMU, Dhaka, Bangladesh, enrolling 201 participants aged ≥13 years using purposive sampling. A rigorous forward–backward translation procedure was employed. Content validity was evaluated through expert review. Construct validity was assessed via exploratory factor analysis, and convergent validity was tested by correlating C-SSRS scores with Beck Depression Inventory-II (BDI-II) scores. Internal consistency was measured using Cronbach’s alpha, and predictive accuracy was assessed through sensitivity and specificity analysis. Result: The sample included adolescents (50.2%) and adults (49.8%) with and without suicidal behavior. Content validity indices (I-CVI) were ≥0.83 for all items. Factor analyses supported the structural validity of the scale, with acceptable variance explained across subscales: severity (61.85–69.93%), intensity (53.76–73.93%), and behavior (41.93–47.9%). Cronbach’s alpha values ranged from 0.523 to 0.76 across subscales and age groups. Convergent validity was stronger for recent (past one-month) suicidal ideation and intensity (r = 0.686 and r = 0.406, p < 0.01) compared to lifetime measures. Sensitivity for detecting suicidal behaviors was high (92.9%–100%), while specificity ranged from 18.3% to 40%. Conclusion: The Bangla version of the C-SSRS Lifetime/Recent – Clinical version is a reliable, valid, and culturally appropriate tool for assessing suicidal ideation and behavior among both adolescents and adults in Bangladesh. Its use may significantly enhance suicide prevention efforts in clinical and research settings.